Delayed Slipped Capital Femoral Epiphysis After Treatment of Femoral Neck Fracture in Children. Issue 8 (August 2015) - Li, Hai; Zhao, Li; Huang, Luyu; Kuo, Ken N
Abstract: Background: Slipped capital femoral epiphysis (SCFE) after the treatment of femoral neck fracture is a rare entity in children that poses important treatment challenges. Case Description: We describe the presentation and management of two patients, a 12‐year‐old girl and a 6‐year‐old girl, each of whom developed SCFE at 5 months and 9 months, respectively, after operative treatment of femoral neck fracture. Literature Review: Five similar cases have been reported in the literature. Along with our two case studies, the average age of all seven patients was 8.9 years (range, 3.6‐12 years; boys, 8.9 years; girls, 9 years). None of the children was in a high weight percentile or had any known endocrinologic disorder. Two had asymptomatic mild SCFE, whereas the others felt unexplained pain with ambulation when the slippage was brought to their attention. Although it is not possible to prove a causal relationship between the initial fracture and the subsequent SCFE, clinical factors such as implant irritation, early return to weightbearing, delayed union or nonunion, coxa vara, and avascular necrosis warrant consideration as potentially related to the subsequent slip. Clinical Relevance: The onset of SCFE after surgical treatment of a femoral neck fracture may reflect inadequate treatment of the fracture. For best practice, we should perform a gentle anatomic reduction, appropriate internal fixation for femoral neck fracture in skeletally immature patients. Postoperative cast immobilization and delayed weightbearing are also important to avoid complication. It is essential for pediatric orthopaedic surgeons to be aware of this clinical scenario to allow prompt recognition and patient treatment.